A psychometric analysis for the adaptation of the comprehensive breast cancer knowledge test for the male population: a methodological study - Gencbas, Dercan; Ozdemir, Serpil; Yaman Uzumcu, Leyla; Bulut, Yunus Emre (Frontiers in Public Health, 2025)
ObjectiveIncreasing men’s knowledge and awareness of breast cancer is aimed at addressing a significant barrier to women’s engagement in screening. This study aims to adapt the Breast Cancer Knowledge Test, originally designed for women, for use with men, in order to increase their awareness and support female screening efforts.MethodsThis methodological study was conducted with 310 male volunteers. The Davis technique was utilized to evaluate content validity to adapt the Breast Cancer Knowledge Test for males. The construct validity of the scale was evaluated using Tetrachoric Factor Analysis. Kuder Richardson-20 was calculated to determine the reliability of the scale. Item difficulty and discrimination indices were tested using Rasch analysis.ResultsThe Content Validity Index value was 0.96. The data was suitable for the factor analysis according to Bartlett’s statistics (p = 0.001) and Kaiser-Meyer-Olkin test (test = 0.92). In the tetrachoric factor analysis, there were two subscales, explaining the total variance of 60.94%, and the goodness of fit indices were evaluated as indicating “excellent fit.” According to the Rasch analysis, the model was found to be significant (p < 0.05), and the infit and outfit values were within the range of 0.5 to 1.5.ConclusionThe male version of the Breast Cancer Knowledge Test was a valid and reliable tool for assessing the knowledge level of the Turkish male population regarding female breast cancer. By identifying areas where men lack knowledge, this scale can inform the development of targeted public health and educational initiatives, ultimately improving male engagement in breast cancer awareness and supporting female screening efforts.